Ecological rod for water retention and sand fixation and preparation method thereof

By using materials such as polylactic acid, polyadipic acid/butylene terephthalate and modified corn starch, the high cost and limited effect of soil erosion and desertification problems in the prior art are solved, and the problem of high quality and limited effect is achieved. Efficient and sustainable sand-fixing and water retention effects, and maintain good windproof and water retention performance in strict environments, so as not to pollute the environment after degradation.

CN119161879AActive Publication Date: 2024-12-20CHINA ACADEMY OF RAILWAY SCI CORP LTD +3
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411299373.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-20
Estimated Expiration
2044-09-18

AI Technical Summary

Technical Problem

Existing ecological restoration technologies have problems such as high cost, limited effect and difficulty in degradation when solving soil erosion and desertification problems, and are difficult to promote and apply on a large scale.

Method used

Using columnar shells prepared from materials such as polylactic acid (PLA), polyadipic acid/butylene terephthalate (PBAT), modified corn starch and maleic anhydride, combined with water retention agent and growth substrate ecological rods, Manufactured by melt blending and injection molding pressing processes, it forms a degradable, environmentally friendly sand-fixing and water-retaining material.

Benefits of technology

It achieves economical, efficient and sustainable soil and sand fixation effects, promotes plant growth, and maintains good windproof and water retention performance in strict environments, so as not to pollute the environment after degradation.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a water-retaining and sand-fixing ecological rod and a preparation method thereof, and the water-retaining and sand-fixing ecological rod is prepared from the following raw materials: a columnar shell and an internal filler. The columnar shell is prepared from the following raw materials in parts by weight: 70-90 parts of PLA, 10-20 parts of PBAT, 5-15 parts of modified corn starch, 1-3 parts of an initiator and 2-6 parts of maleic anhydride. The internal filler is prepared from the following raw materials: a water-retaining agent and a growth base material. The prepared ecological rod for water retention and sand fixation is good in water retention performance, has a certain sand blocking and sand fixation effect, also has a certain growth base material, can promote plant growth, and is especially suitable for growth of plants in severe environments such as cold, dry and saline-alkali soil areas.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ecological restoration, and in particular relates to an ecological stick for retaining water and fixing sand and a preparation method thereof. Background Art

[0002] With the continuous intensification of global climate change and human activities, soil erosion and desertification have become serious ecological and environmental problems worldwide. Soil erosion leads to the decline of soil fertility and the siltation of rivers and lakes, which seriously affects agricultural production and ecosystem functions; while desertification further aggravates the waste of land resources and the occurrence of wind and sand disasters, posing a serious threat to the ecological environment and economic development of surrounding areas.

[0003] At present, a variety of ecological restoration technologies have been proposed and applied to address the above problems, such as vegetation restoration, soil improvement, and engineering sand fixation. However, these methods often have problems such as high cost, limited effect, and difficulty in long-term maintenance in practical applications. Therefore, it is particularly important to develop an economical, efficient, and sustainable water conservation and sand fixation technology.

[0004] The water-retaining and sand-fixing ecological stick is a new type of ecological restoration material that came into being under this background. It processes plant soil, fertilizer, seeds and other nutrient materials into a tubular structure through a special process. It not only has a good soil-fixing effect, but also can effectively retain soil moisture and promote plant growth, thereby achieving effective control of soil erosion and desertification.

[0005] Although existing ecological restoration technologies have alleviated the problems of soil erosion and desertification to a certain extent, they still have the following shortcomings: High cost: Some technologies require high material costs and construction costs, making them difficult to promote and apply on a large scale. Limited effect: Although some technologies can improve soil conditions in the short term, the long-term effect is not ideal and it is difficult to maintain the stability of the ecosystem. Difficult to degrade: Some sand-fixing materials are difficult to degrade and may cause secondary pollution to the soil and groundwater.

[0006] In view of the shortcomings of the prior art, the present invention aims to provide an economical, efficient and sustainable water-retaining and sand-fixing ecological stick and its preparation and application method. The ecological stick can not only effectively fix sand and retain water, promote plant growth, but also has the advantages of easy degradation and environmental friendliness, providing a new solution for the control of soil erosion and desertification. Summary of the invention

[0007] The purpose of the present invention is to provide an ecological stick for water retention and sand fixation and a preparation method thereof. The ecological stick for water retention and sand fixation can not only effectively fix sand and retain water, but also promote plant growth, is easily degradable, and is environmentally friendly, thus providing a new solution to the control of soil erosion and desertification problems.

[0008] The invention provides an ecological stick for retaining water and fixing sand, and its preparation raw materials include a columnar shell and internal fillings.

[0009] The raw materials for preparing the columnar shell include the following components by weight: 70 to 90 parts of polylactic acid (PLA), 10 to 20 parts of polybutylene adipate / terephthalate (PBAT), 5 to 15 parts of modified corn starch, 1 to 3 parts of initiator, and 2 to 6 parts of maleic anhydride.

[0010] Preferably, the PLA has a melt index of 1 to 5 g / 10 min at 190° C., a tensile strength of 30 to 35 MPa, a flexural strength of 53 to 56 MPa, and a flexural modulus of 2600 to 2800 MPa.

[0011] In some preferred embodiments, the PLA is purchased from Zibo Tianju Hongchuan New Material Technology, THJS-8801-1.

[0012] Preferably, the elongation at break of the PBAT is ≥300%, the melt index at 190°C is 1-5g / 10min, and the Vicat softening temperature is ≥80°C; further preferably, the elongation at break of the PBAT is ≥400%, the melt index at 190°C is 2.5-4.5g / 10min, and the Vicat softening temperature is ≥80°C.

[0013] In some preferred embodiments, the PBAT is purchased from Xinjiang Blue Mountain Tunhe Chemical Industry, TH-801T.

[0014] The preparation method of the modified corn starch comprises the following steps: vacuum drying the corn starch at 70-90° C. to constant weight, adding a modifier, stirring evenly and sealing, vacuum drying at 70-90° C. for 5-8 hours and then taking out, and melt blending at 110-130° C. to obtain the modified corn starch.

[0015] Preferably, the amount of the modifier added is 20-30% of the corn starch.

[0016] Preferably, the modifiers are glycerol and sorbitol.

[0017] Preferably, the mass ratio of glycerol to sorbitol is 1:(0.5-2); further preferably, it is 1:1.

[0018] In practical applications, the requirements for the columnar shell of the eco-stick are relatively high, and it needs to have certain toughness and water resistance, which helps the eco-stick to maintain a stable shape when subjected to wind, is not easy to break, improves its windproof performance, and does not absorb too much water, thereby improving its water retention performance. In addition, the shell should preferably be a degradable material, which will not cause long-term pollution to the environment after use, and the degraded product can also be used as a fertilizer to provide nutrients for plant growth. Corn starch is a natural biodegradable material with a low price, but its own structural limitations make it impossible to process and shape it by a melting method. The inventors found that the use of glycerol and sorbitol with a mass ratio of 1: (0.5-2) as modifiers to modify corn starch can improve the mechanical properties of the columnar shell of the eco-stick while also improving the processing performance. This may be because the two modifiers work synergistically to destroy the original crystalline structure of starch, making the starch molecules loose, thereby improving the thermoplasticity of starch, enabling it to be processed and shaped by a melting method, thereby improving the various properties of the columnar shell of the molded eco-stick. At the same time, the two substances will also react with starch to form new bonds, further enhancing the strength of starch, and the smaller propylene glycol molecules also have a certain lubricating effect, thereby further improving the processing performance. The inventors found in actual experiments that although propylene glycol has a better plasticizing effect than sorbitol and can improve the biodegradability of the columnar shell, its excessive addition will cause corn starch to be over-plasticized, and molecules are more likely to slip, resulting in a decrease in tensile strength, affecting the mechanical properties of the eco-stick columnar shell. Even if corn starch is modified, its compatibility with PLA and PBAT is still poor, and the three substances are only physically blended, which affects the performance of the eco-stick finally prepared.

[0019] Preferably, the mass ratio of PLA, PBAT and modified corn starch is (7-9):(1-2):1; more preferably, it is 16:3:2.

[0020] Preferably, the initiator is benzoyl peroxide.

[0021] The inventors found that by selecting a specific PBAT, and the mass ratio of the PLA, PBAT and modified corn starch is (7-9): (1-2): 1, and introducing maleic anhydride at the same time, it is possible to improve the mechanical properties of the prepared columnar shell while improving its water resistance, thereby improving the windproof and water-retaining properties of the eco-stick. This may be because on the one hand, the chain segments of PLA will form an interpenetrating network structure with the chain segments of PBAT, thereby enhancing the interaction force between molecules, and can also change the crystallization behavior of PBAT, thereby improving the mechanical properties of the columnar shell. On the other hand, the filling effect and interfacial interaction of the modified corn starch can not only reduce the movement of the PBAT chain segments, thereby improving the mechanical properties of the columnar shell, but also can be compounded with PLA to hinder the penetration of water molecules to a certain extent, improve the water resistance of the composite material, and improve the barrier properties of the columnar shell. However, excessive addition of corn starch will greatly reduce the melt strength, which is not conducive to the processing and molding of materials to obtain a columnar shell. In addition, the introduction of an appropriate amount of maleic anhydride can not only promote the grafting reaction of glycerol on the molecular chain of corn starch, but also enhance the interfacial bonding force between PLA, PBAT and modified corn starch, promote the grafting effect of corn starch and polymer, improve the interaction between the two phases, increase the compatibility of corn starch in the system, form a three-dimensional network structure through cross-linking reaction, reduce the permeation channel of water molecules, and thus improve the various properties of the columnar shell. However, if the amount of maleic anhydride added is too high, its own molecules will interact with each other, which is not conducive to the dispersion of corn starch in the system, thereby affecting the molding effect, and then affecting the various properties of the final columnar shell.

[0022] The preparation method of the columnar shell comprises the following steps: drying the raw materials and mixing them evenly, extruding them after melt blending to obtain pellets, and crushing the pellets and then performing injection molding to obtain the pellets.

[0023] Preferably, the melt blending temperature is 175-190° C., and the rotation speed is 30-50 r / min.

[0024] Preferably, the injection molding pressure is 8-12 MPa, and the injection molding temperature is 170-180°C.

[0025] The internal filling material and its preparation raw materials include a water retaining agent and a growth substrate.

[0026] The added amount of the water retaining agent is 2% to 5% of the mass of the growth substrate.

[0027] The preparation method of the water retaining agent comprises the following steps: uniformly dispersing polysuccinimide in water, adding a proper amount of crosslinking agent, stirring at 35-40°C and adding sodium hydroxide solution until the pH value is 8-9, cooling the solution to room temperature after it becomes clear and transparent, adding modified attapulgite, acrylamide, acrylic acid and sodium alginate, stirring uniformly and heating to 60-70°C, adding potassium persulfate, continuing stirring for 3-5h, drying and crushing to obtain the water retaining agent.

[0028] Preferably, the average molecular weight of the polysuccinimide is 8,000 to 10,000.

[0029] In some preferred embodiments, the polysuccinimide is purchased from Shanghai MacLean Biochemical Technology Co., Ltd.

[0030] Preferably, the mass ratio of the polysuccinimide to water is 1:(20-40).

[0031] Preferably, the crosslinking agent is γ-aminopropyltriethoxysilane (KH550) and γ-methacryloxypropyltrimethoxysilane (KH570).

[0032] Preferably, the mass ratio of KH550 to KH570 is 1:(0.5-2); more preferably, it is 1:1.

[0033] Preferably, the added amount of the crosslinking agent is 1.5-2 mol % of the polysuccinimide.

[0034] Preferably, the concentration of the sodium hydroxide solution is 1 mol / L.

[0035] The preparation method of modified attapulgite comprises the following steps: dissolving an attapulgite modifier in an ethanol aqueous solution with a concentration of 80 wt%, adding attapulgite, stirring at 75-85° C. for 2-4 hours, filtering, and drying at 100° C. for 12 hours to obtain the modified attapulgite.

[0036] Preferably, the attapulgite modifier is sodium dodecylbenzene sulfonate and hexadecyltrimethylammonium chloride.

[0037] Preferably, the mass ratio of the sodium dodecylbenzene sulfonate to hexadecyltrimethylammonium chloride is 1:(1-3); further preferably, it is 1:2.

[0038] Preferably, the mass ratio of the modifier to the ethanol aqueous solution is 1:25-35; more preferably, it is 1:30.

[0039] Preferably, the adsorption rate of the attapulgite is 32%, the compressive strength is 80 MPa, and the particle size is 0.01 μm.

[0040] In some preferred embodiments, the attapulgite is purchased from Lingshou County Malin Mineral Products Processing Plant.

[0041] Preferably, the mass ratio of the attapulgite to the modifier is 1:1-2; more preferably, it is 2:3.

[0042] In some preferred schemes, adding a certain amount of attapulgite can improve the sand-fixing and water-retaining performance of the water-retaining agent while also improving its heat and weather resistance. This is because attapulgite has a unique rod-shaped crystal structure, which can increase the porosity and specific surface area of ​​the soil, thereby providing more water storage space. The excellent physical and chemical stability of attapulgite helps the soil maintain its structural and functional stability under extreme climatic conditions and improves the weather resistance and temperature resistance of the soil. In addition, attapulgite can also regulate the pH of the soil to keep it within a suitable range, which is beneficial to the activity of soil microorganisms and the growth of plants, and then helps the soil maintain its ecological balance and stability under different climatic conditions. However, the compatibility between attapulgite and high molecular polymers is poor, and agglomeration is prone to occur in the system, affecting the effect.

[0043] The inventor found that the use of sodium dodecylbenzene sulfonate and hexadecyltrimethylammonium chloride to modify attapulgite can not only improve the compatibility between attapulgite and high molecular polymer, but also further improve the water retention and sand fixation effect. This may be because sodium dodecylbenzene sulfonate and hexadecyltrimethylammonium chloride synergistically act on the surface of attapulgite by physical adsorption and chemical bonding, change its surface properties, form a layer of organic film on the surface of attapulgite, and help enhance the compatibility with high molecular polymer. Sodium dodecylbenzene sulfonate and hexadecyltrimethylammonium chloride are inserted into the interlayer structure of attapulgite by intercalation on the one hand, increase the interlayer spacing, make the combination between soil particles more closely, and also help to form a closer combination with high molecular polymer, on the other hand, its hydrophilic end and hydrophobic end form a kind of equilibrium state in the soil, which not only ensures the hydrophilicity of the soil so as to store water, but also reduces the evaporation of water and the flow of sand particles through the hydrophobic network.

[0044] Preferably, the molar ratio of polysuccinimide, acrylamide and acrylic acid is 1:(0.5-2):(2-4); more preferably, it is 1:1:3.

[0045] The inventors found that the water-retaining agent prepared by using specific polysuccinimide, acrylamide and acrylic acid as raw materials can not only improve the water-retaining and sand-fixing functions of the eco-stick, but also promote plant growth. This is because the molecular chains of the three polymers are intertwined and cross-linked during the composite process to form a stable three-dimensional network structure. This structure not only improves the mechanical strength of the hydrogel, but also enhances its water-retaining and sand-fixing capabilities. The hydrophilic groups such as carboxyl and hydroxyl groups of polyaspartic acid interact with the polar groups of polyacrylamide and polyacrylic acid to form more hydrogen bonds and ionic bonds, thereby improving the water absorption and stability of the hydrogel. In addition, the water-retaining agent releases nutrients such as polyaspartic acid during the degradation process, which can be absorbed and utilized by plants to promote the growth and development of plants. At the same time, the degradation products are harmless to the environment and meet the requirements of green chemistry. However, only these three polymers have poor weather resistance, and will be affected by thermal oxidative aging and photooxidative aging, resulting in chain breakage and cross-linking reactions, which affect the wind-proof and sand-fixing performance.

[0046] Preferably, the added amount of the modified attapulgite is 3% to 5% of the total mass of polysuccinimide, acrylamide and acrylic acid.

[0047] Preferably, the amount of sodium alginate used is 1% to 2% of the total mass of polysuccinimide, acrylamide and acrylic acid.

[0048] Preferably, the amount of potassium persulfate used is 1% to 2% of the total mass of acrylamide and acrylic acid.

[0049] Preferably, the growth substrate is soil.

[0050] The method for preparing the water-retaining and sand-fixing ecological stick comprises the following steps: filling the internal filling material into the columnar outer shell.

[0051] In some preferred schemes, the diameter of the water-retaining and sand-fixing ecological rod is 10 to 15 cm, and cold-resistant, cold-tolerant, salt-alkali-tolerant and other shrub plants are cultivated inside. Under the action of the ecological rod, the plants can grow smoothly, and after the plants grow, they can play the role of sand blocking and sand fixing. It is very suitable for promotion and use, and is of great significance for protecting the environment and controlling soil erosion and desertification.

[0052] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0053] 1. The present invention provides an ecological stick for retaining water and sand, which can not only effectively retain sand and water, but also promote plant growth, is easily degradable, and is environmentally friendly, providing a new solution to the problems of soil erosion and desertification.

[0054] 2. The present invention uses glycerol and sorbitol in a mass ratio of 1: (0.5-2) as modifiers to modify corn starch, which can improve the mechanical properties of the ecological rod-shaped shell while also improving the processing performance.

[0055] 3. The present invention selects a specific PBAT, and the mass ratio of PLA, PBAT and modified corn starch is (7-9): (1-2): 1, and maleic anhydride is introduced, which can improve the mechanical properties of the prepared columnar shell while improving its water resistance, thereby improving the windproof and water-retaining properties of the eco-stick.

[0056] 3. The present invention uses specific polysuccinimide, acrylamide and acrylic acid as raw materials to prepare the water-retaining agent, which can not only improve the water-retaining and sand-fixing function of the eco-stick, but also promote plant growth.

[0057] 4. The present invention uses attapulgite as one of the raw materials, which can improve the sand-fixing and water-retaining performance of the water-retaining agent while also improving its heat-resistance and weather-resistance.

[0058] 5. The present invention uses sodium dodecylbenzene sulfonate and hexadecyltrimethylammonium chloride to modify attapulgite, which can not only improve the compatibility between attapulgite and high molecular polymer, but also further improve the water conservation and sand fixation effect. DETAILED DESCRIPTION

[0059] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0060] The raw materials used in the present invention are all commercially available, specifically:

[0061] PLA, with a melt index of 1-5 g / 10 min at 190 °C, a tensile strength of 30-35 MPa, a flexural strength of 53-56 MPa, and a flexural modulus of 2600-2800 MPa, was purchased from Zibo Tianju Hongchuan New Material Technology, THJS-8801-1.

[0062] PBAT, elongation at break ≥400%, melt index 2.5-4.5 g / 10 min at 190°C, Vicat softening temperature ≥80°C, purchased from Xinjiang Lanshan Tunhe Chemical Industry, TH-801T.

[0063] Polysuccinimide, with an average molecular weight of 8000-10000, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.

[0064] Attapulgite, with an adsorption rate of 32%, a compressive strength of 80 MPa, and a particle size of 0.01 μm, was purchased from Malin Mineral Products Processing Plant in Lingshou County.

[0065] Example 1

[0066] This embodiment provides an ecological stick for retaining water and fixing sand, and the raw materials for preparing the ecological stick are a columnar shell and an internal filler.

[0067] The raw materials for preparing the columnar shell include the following components by weight: 80 parts of PLA, 15 parts of PBAT, 10 parts of modified corn starch, 2 parts of initiator, and 4 parts of maleic anhydride.

[0068] The preparation method of the modified corn starch comprises the following steps: vacuum drying the corn starch at 8°C to constant weight, adding a modifier, stirring evenly and sealing, vacuum drying at 80°C for 7h and then taking out, and blending at 120°C to obtain the modified corn starch.

[0069] The added mass of the modifier is 25% of the corn starch.

[0070] The modifiers are glycerol and sorbitol.

[0071] The mass ratio of the glycerol to sorbitol is 1:1.

[0072] The initiator is benzoyl peroxide.

[0073] The preparation method of the columnar shell comprises the following steps: drying the raw materials and mixing them evenly, extruding them after melt blending to obtain pellets, and crushing the pellets and then performing injection molding to obtain the pellets.

[0074] The melt blending temperature is 180° C. and the rotation speed is 40 r / min.

[0075] The injection molding pressure is 10 MPa, and the injection molding temperature is 190°C.

[0076] The internal filler is prepared from raw materials including a water retaining agent and a growth substrate.

[0077] The amount of the water retaining agent added is 3% of the mass of the growth substrate.

[0078] The preparation method of the water retaining agent comprises the following steps: uniformly dispersing polysuccinimide in water, adding a proper amount of cross-linking agent, stirring at 38°C and adding sodium hydroxide solution until the pH value is 8.5, cooling the solution to room temperature after it becomes clear and transparent, adding modified attapulgite, acrylamide, acrylic acid and sodium alginate, stirring uniformly and heating to 65°C, adding potassium persulfate, continuing stirring for 4 hours, and drying and crushing the solution.

[0079] The mass ratio of the polysuccinimide to water is 1:30.

[0080] The cross-linking agents are KH550 and KH570.

[0081] The mass ratio of KH550 to KH570 is 1:1.

[0082] The added amount of the crosslinking agent is 1.5 mol% of the polysuccinimide.

[0083] The concentration of the sodium hydroxide solution is 1 mol / L.

[0084] The preparation method of the modified attapulgite comprises the following steps: dissolving an attapulgite modifier in an ethanol aqueous solution with a concentration of 80 wt%, adding attapulgite, stirring at 80° C. for 3 h, filtering, and drying at 100° C. for 12 h to obtain the modified attapulgite.

[0085] The attapulgite modifiers are sodium dodecylbenzene sulfonate and hexadecyltrimethylammonium chloride.

[0086] The mass ratio of the sodium dodecylbenzene sulfonate to hexadecyltrimethylammonium chloride is 1:2.

[0087] The mass ratio of the modifier to the ethanol aqueous solution is 1:30.

[0088] The mass ratio of the attapulgite to the modifier is 2:3.

[0089] The molar ratio of the polysuccinimide, acrylamide and acrylic acid is 1:1:3.

[0090] The added amount of the modified attapulgite is 4% of the total mass of polysuccinimide, acrylamide and acrylic acid.

[0091] The amount of sodium alginate used is 1.5% of the total mass of polysuccinimide, acrylamide and acrylic acid.

[0092] The amount of potassium persulfate used is 1.2% of the total mass of acrylamide and acrylic acid.

[0093] The growth substrate is soil.

[0094] The method for preparing the water-retaining and sand-fixing ecological stick comprises the following steps: filling the internal filling material into the columnar outer shell.

[0095] Example 2

[0096] The difference between this embodiment and embodiment 1 is that the raw materials for preparing the columnar shell include the following components by weight: 70 parts of PLA, 10 parts of PBAT, 10 parts of modified corn starch, 2 parts of initiator, and 4 parts of maleic anhydride.

[0097] Example 3

[0098] The difference between this embodiment and embodiment 1 is that the molar ratio of polysuccinimide, acrylamide and acrylic acid is 1:2:3.

[0099] Comparative Example 1

[0100] The difference between this comparative example and Example 1 is that the raw materials for preparing the columnar shell include the following components by weight: 60 parts of PLA, 15 parts of PBAT, 10 parts of modified corn starch, 2 parts of initiator, and 4 parts of maleic anhydride.

[0101] Comparative Example 2

[0102] The difference between this comparative example and Example 1 is that the raw materials for preparing the columnar shell include the following components by weight: 80 parts of PLA, 15 parts of PBAT, 10 parts of modified corn starch, 2 parts of initiator, and 10 parts of maleic anhydride.

[0103] Comparative Example 3

[0104] The difference between this comparative example and Example 1 is that the modifier is glycerol.

[0105] Comparative Example 4

[0106] The difference between this comparative example and Example 1 is that the attapulgite modifier is sodium dodecylbenzene sulfonate.

[0107] Comparative Example 5

[0108] The difference between this comparative example and Example 1 is that the preparation method of the water retaining agent comprises the following steps: uniformly dispersing polysuccinimide in water, adding an appropriate amount of a cross-linking agent, stirring at 38°C and adding a sodium hydroxide solution until the pH value is 8.5, cooling the solution to room temperature after it becomes clear and transparent, adding attapulgite, acrylamide, acrylic acid and sodium alginate, stirring evenly and heating to 65°C, adding potassium persulfate, continuing stirring for 4 hours, and drying and crushing to obtain the water retaining agent.

[0109] Comparative Example 6

[0110] The difference between this comparative example and Example 1 is that the preparation method of the water retaining agent comprises the following steps: uniformly dispersing polysuccinimide in water, adding an appropriate amount of a cross-linking agent, stirring at 38°C and adding a sodium hydroxide solution until the pH value is 8.5, cooling the solution to room temperature after the solution becomes clear and transparent, adding modified attapulgite, acrylic acid and sodium alginate, stirring uniformly and heating to 65°C, then adding potassium persulfate, continuing stirring for 4 hours, and drying and crushing to obtain the water retaining agent.

[0111] The molar ratio of the polysuccinimide to acrylic acid is 1:3.

[0112] The added amount of the modified attapulgite is 4% of the total mass of polysuccinimide and acrylic acid.

[0113] The amount of sodium alginate used is 1.5% of the total mass of polysuccinimide and acrylic acid.

[0114] The amount of potassium persulfate used is 1.2% of the mass of acrylic acid.

[0115] Comparative Example 7

[0116] The difference between this comparative example and Example 1 is that the molar ratio of polysuccinimide, acrylamide and acrylic acid is 1:3:5.

[0117] Performance Testing

[0118] The internal filling and the columnar shell are completely immersed in water. After soaking until the mass does not change, they are taken out and put into the columnar shell, and the mass M1 at this time is measured. The water-saturated internal filling is put into the columnar shell and placed in an environment with a temperature of 50°C, a relative humidity of 0, and a light intensity of 100%. After 7 days, its mass M2 is tested. The mass loss rate = (M1-M2) / M1×100%. The lower the mass loss rate, the better the water retention performance. Referring to the method of patent 202110090064.5, alfalfa seeds were placed in a water-saturated eco-stick for cultivation, and the external environmental conditions were set as follows: temperature of 50°C, relative humidity of 0, and light intensity of 100%. The germination rate of seeds was recorded for 30 days. The results are shown in Table 1.

[0119] Table 1 Measurement results

[0120] Mass loss rate / % Germination rate / % Example 1 13.8 95.8 Example 2 14.2 95.4 Example 3 14.3 95.3 Comparative Example 1 18.6 90.5 Comparative Example 2 19.1 89.7 Comparative Example 3 17.5 92.1 Comparative Example 4 20.1 90.3 Comparative Example 5 28.3 78.8 Comparative Example 6 22.9 84.6 Comparative Example 7 19.7 88.5

[0121] According to statistics, the water-retaining and sand-fixing eco-sticks prepared in Examples 1 to 3 of the present invention have a low mass loss rate in harsh environments and a high plant germination rate. In Comparative Example 1, the amount of PLA added is too little, in Comparative Example 2, the amount of maleic anhydride added is too much, in Comparative Example 3, no sorbitol modifier is added, in Comparative Example 4, no hexadecyltrimethylammonium chloride attapulgite modifier is added, in Comparative Example 5, attapulgite is not modified, in Comparative Example 6, no acrylamide is added, in Comparative Example 7, excessive acrylamide and acrylic acid are added, and the mass loss rate of the prepared eco-sticks is high and the seed germination rate is low. Therefore, the water-retaining and sand-fixing eco-sticks prepared by the raw materials and methods described in this application can not only effectively fix sand and retain water, but also promote plant growth, are easily degradable, and are environmentally friendly, providing a new solution for the control of soil erosion and desertification problems.

[0122] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. An ecological stick for retaining water and fixing sand, It is characterized in that The raw materials for its preparation include, by weight, a columnar shell and an internal filler; The raw materials for preparing the columnar shell include the following components by weight: 70-90 parts of PLA, 10-20 parts of PBAT, 5-15 parts of modified corn starch, 1-3 parts of initiator, and 2-6 parts of maleic anhydride; the PLA has a melt index of 1-5 g / 10 min at 190° C., a tensile strength of 30-35 MPa, a flexural strength of 53-56 MPa, and a flexural modulus of 2600-2800 MPa; the PBAT has an elongation at break of ≥300%, a melt index of 1-5 g / 10 min at 190° C., and a Vicat softening temperature of ≥80° C. The raw materials for preparing the internal filling material include a water retaining agent and a growth substrate; The preparation method of the water retaining agent comprises the following steps: uniformly dispersing polysuccinimide in water, adding a proper amount of crosslinking agent, stirring at 35-40°C and adding sodium hydroxide solution until the pH value is 8-9, cooling the solution to room temperature after it becomes clear and transparent, adding modified attapulgite, acrylamide, acrylic acid and sodium alginate, stirring uniformly and heating to 60-70°C, adding potassium persulfate, continuing stirring for 3-5h, drying and crushing to obtain the water retaining agent.

2. The water-retaining and sand-fixing ecological stick according to claim 1, It is characterized in that The preparation method of the modified corn starch comprises the following steps: vacuum drying the corn starch at 70-90° C. to constant weight, adding a modifier, stirring evenly and sealing, vacuum drying at 70-90° C. for 5-8 hours and then taking out, and melt blending at 110-130° C. to obtain the modified corn starch.

3. The water-retaining and sand-fixing ecological stick according to claim 2, It is characterized in that The modifiers are glycerol and sorbitol.

4. The water-retaining and sand-fixing ecological stick according to claim 1, It is characterized in that The mass ratio of the PLA, PBAT and modified corn starch is (7-9):(1-2):

1.

5. The water-retaining and sand-fixing ecological stick according to claim 1, It is characterized in that The preparation method of the columnar shell comprises the following steps: drying the raw materials and mixing them evenly, extruding them after melt blending to obtain pellets, and crushing the pellets and then performing injection molding to obtain the pellets.

6. The water-retaining and sand-fixing ecological stick according to claim 1, It is characterized in that The average molecular weight of the polysuccinimide is 8000-10000.

7. The water-retaining and sand-fixing ecological stick according to claim 1, It is characterized in that The preparation method of modified attapulgite comprises the following steps: dissolving an attapulgite modifier in an ethanol aqueous solution with a concentration of 80 wt%, adding attapulgite, stirring at 75-85° C. for 2-4 hours, filtering, and drying at 100° C. for 12 hours to obtain the modified attapulgite.

8. The water-retaining and sand-fixing ecological stick according to claim 7, It is characterized in that The attapulgite modifiers are sodium dodecylbenzene sulfonate and hexadecyltrimethylammonium chloride.

9. The method for preparing the water-retaining and sand-fixing ecological stick according to claim 1, It is characterized in that The growth substrate is soil.

10. A method for preparing the water-retaining and sand-fixing ecological stick according to any one of claims 1 to 9, It is characterized in that The steps are as follows: filling the internal filling material into the columnar outer shell.

Citation Information

Patent Citations

  • Ecological rod and application thereof

    CN112400546A

  • Starch modified PBAT / PLA biodegradable plastic film and preparation method thereof

    CN113861635A

  • Soil improving composition and soil improving method using the same

    JP2012201766A

  • Fertilizer of Geo-Pipe Type Using Corn Starch

    KR101512269B1